Combined Use of cyclinD1 and Ki67 for Prognosis of Luminal-Like Breast Cancer Patients - Hao, Junmei; Zhang, Wenfeng; Lyu, Yan; Zou, Jiarui; Zhang, Yunyun; Lyu, Jiahong; Zhang, Jianbo; Xie, Shuishan; Zhang, Cuiping; Zhang, Jiandi; Tang, Fangrong (Frontiers in Oncology, 2021)
Background: Ki67 is a biomarker of proliferation to be used in immunohistochemistry (IHC)-based surrogate assay to determine the necessity of cytotoxic therapy for Luminal-like breast cancer patients. CyclinD1 is another frequently used biomarker of proliferation. A retrospective study was performed here to investigate if these two biomarkers may be combined to improve the prognosis of Luminal-like patients. Methods: Both Ki67 and cyclinD1 protein levels were measured absolutely and quantitatively using Quantitative Dot Blot (QDB) method in 143 Luminal-like specimens. Optimized cutoffs for these two biomarkers were developed to evaluate their prognostic role using Kaplan-Meier overall survival (OS) analysis. Results: CyclinD1 was found as an independent prognostic factor from Ki67 in univariate and multivariate OS analyses. At optimized cutoffs (cyclinD1 at 0.44 mole/g & Ki67 at 2.31nmole/g), the subgroup with both biomarkers below the cutoffs (n=65) had 10-year survival probability at 90%, in comparison to those with both biomarkers above the cutoffs (n=18) with 8-year survival probability at 26% (Log rank test p<0.0001). This finding was used to modify surrogate assay using IHC-based cyclinD1 scores, with p value decreased from 0.031 to 0.00061, or from 0.1 to 0.02, when Ki67 score of 14% or 20% was used as cutoff respectively in surrogate assay. Conclusion: Current study supports prospective investigation of cyclinD1 relevance in the clinic..